A new chaotic jerk system with two quadratic nonlinearities and its applications to electronic circuit implementation and image encryption. (2018) - Vaidyanathan, Sundarapandian; Akgul, Akif; Kacar, Sezgin
This work presents a new chaotic jerk system having two quadratic nonlinearities. Dynamical properties of the new jerk system are discovered through dissipativity, equilibrium point analysis, eigenvalues of the Jacobian matrices, bifurcation diagram, and Lyapunov exponents. The results also show that the new jerk system has interesting complex dynamics characteristics. Furthermore, random number generator (RNG), its NIST-800-22 tests, an image encryption application and its security analyses are realised with the new jerk system. The new chaotic jerk system can be useful in scientific fields such as physics, control, true and pseudo random number generator (TRNG, PRNG), artificial neural network, genetic algorithm etc.